2007
DOI: 10.1044/1092-4388(2007/076)
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Receptive and Expressive Vocabulary, Listening Comprehension, Pre-Reading Skills, Word Identification Skills, and Reading Comprehension by Children With Reading Disabilities

Abstract: Results are consistent with previous research indicating that oral language skills are related to reading achievement (e.g., A. Olofsson & J. Niedersoe, 1999; H. S. Scarborough, 1990). Results from this study suggest that receptive and expressive vocabulary knowledge influence pre-reading skills in differential ways. Further, results suggest that expressive vocabulary knowledge and listening comprehension skills facilitate word identification skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
1
18

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(180 citation statements)
references
References 31 publications
7
154
1
18
Order By: Relevance
“…Mothers who read more books to their children and those who asked more questions extending the reading did not necessarily have children with greater phonological awareness at the end of preschool. Given the well-documented link between phonological awareness and vocabulary skills (Avons et al, 1998;Bowey, 2001;Gathercole et al, 1999;Jusczyk, 1993;McBride-Chang et al, 2005;Metsala, 1999;Wise et al, 2007), this study contributes to the literature on reading acquisition by determining that, at least for this low-income and ethnically diverse group of families, frequency and quality of book-reading practices are not directly linked to development of phonological awareness even when controlling for children's vocabulary. In the past, studies that found a link between phonological awareness and book-reading practices (Raz & Bryant, 1990) did not control for vocabulary.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mothers who read more books to their children and those who asked more questions extending the reading did not necessarily have children with greater phonological awareness at the end of preschool. Given the well-documented link between phonological awareness and vocabulary skills (Avons et al, 1998;Bowey, 2001;Gathercole et al, 1999;Jusczyk, 1993;McBride-Chang et al, 2005;Metsala, 1999;Wise et al, 2007), this study contributes to the literature on reading acquisition by determining that, at least for this low-income and ethnically diverse group of families, frequency and quality of book-reading practices are not directly linked to development of phonological awareness even when controlling for children's vocabulary. In the past, studies that found a link between phonological awareness and book-reading practices (Raz & Bryant, 1990) did not control for vocabulary.…”
Section: Discussionmentioning
confidence: 96%
“…Children with larger vocabularies have better phonological awareness skills (Avons, Wragg, Cupples, & Lovegrove, 1998;Bowey, 2001;Gathercole, Service, Hitch, Adams, & Martin, 1999;Jusczyk, 1993;McBride-Chang et al, 2005;Metsala, 1999;Wise, Sevcik, Morris, Lovett, & Wolf, 2007). As vocabulary expands, there is growing pressure to discriminate among similar sounding words, which leads to increasingly segmented lexical representations (Metsala & Walley, 1998).…”
Section: Abstract Phonological Awareness Vocabulary Maternal Elabormentioning
confidence: 99%
“…To measure children's reading, we used the Test of Word Reading Efficiency, (TOWRE; , which correlates strongly with children's overall reading performance (Wise et al, 2007), vocabulary (Ricketts et al, 2007), and NWR ability (Nation & Hulme, 2010). Syntactic comprehension was assessed using a task that reveals considerable individual differences in typically developing children's performance (Dick et al, 2004;Leech et al, 2007).…”
Section: The Present Studymentioning
confidence: 99%
“…On a déjà bien attesté l'association entre l'étendue du vocabulaire et le rendement en lecture orale ou en compréhension de la langue écrite (Nation & Cocksey, 2009), que ce dernier soit mesuré concurremment ou ultérieurement (Chiappe, Chiappe, & Gottardo, 2004;Lindsey, Manis, & Bailey, 2003;Sénéchal, Ouellette, & Rodney, 2006). Par ailleurs, Wise, Sevcik, Morris, Lovett et Wolf (2007b) rapportent des résultats qui donnent à penser que l'étendue du vocabulaire expressif pourrait être plus utile que celle du vocabulaire réceptif au dépistage des élèves à risque de difficultés en lecture.…”
Section: Les Faiblesses Dans Le Traitement Du Langage Oralunclassified